ENGLISH TEACHERS’ CHALLENGES IN IMPLEMENTING SCIENTIFIC APPROACH - Ria Rahmiyanti; Hamzah Hamzah; Rusdi Noor Noor (Universitas Negeri Islam Sumatera Utara, 2023)
Abstract : Scientific approach is a teaching strategy which is used in 2013 curriculum in Indonesia. This approach can be implemented in all subjects at senior high school include English. Although scientific approach offers significant effectiveness in teaching and learning process, there were still some challenges faced by English teachers in each five phases. This qualitative descriptive study aims investigating and describing the challenges and solutions in implementing scientific approach experienced by English teachers in Senior high school in Jambi. The data were collected through interview with English teachers. The findings showed that the teachers faced some similar and different challenges in implementing it. Almost in each phase, the teachers faced challenges related to students’ low motivation in learning English because of some factors such as having limited number of vocabulary, getting difficult in constructing idea to do tasks and having no interest in the topics. Then, the teachers also try to do some solutions for solving all the challenges such as giving example from real life, motivating the students in learning English, give them reward or additional score for whom participate actively, listing new vocabulary, and allowing students to asking by mixing Indonesian and English.Key words: Scientific Approach, 2013 Curriculum, Challenges, Senior High School